Pengaruh Senam Lansia Terhadap Kemampuan Fungsional Pada Lansia Yang Mengalami Low Back Pain (Nyeri Punggung) Di Desa Leyangan Kecamatan Ungaran Timur Kabupaten Semarang - I Wayan Widhi Adnyana; Puji Lestari (Jurnal Keperawatan Komunitas, 2014)
The functional ability improvement of elderly people with low back pain (LBP) can be done by several ways. One of them is by geriatric gymnastics. The purpose of this study is to find the influence of geriatric gymnastics toward the functional ability in elderly with low back pain at Leyangan Village East Ungaran Sub-district Semarang Regency. This study used a quantitative approach with quasi-experimental method. This study used non-equivalent (pretest and posttest) control group design. The population in this study was the elderly who had low back pain at Leyangan Village East Ungaran Sub-district Semarang Regency. The population in this was intervention groups with 15 respondents, respectively. Data sampling used Purposive sampling technique, whereas the instrument of functional ability measured by using Barthel index The results of this study indicate that there is a difference in the functional ability of the elderly with low back pain between before and after the geriatric gymnastics given in the intervention group, with the p value (0,001) < α (0,05). There is an influence of geriatric gymnastics toward the functional ability of elderly with low back pain, with p-value of 0,039 < α (0,05). The elderly should keep improving physical fitness, especially the function ability. By implementing the geriatric gymnastics regularly, the elderly can treat the functional ability of the elderly can treat the functional ability of the elderly with low back pain.